(untitled) (Journal of Educational Sciences, 2016)
The article presents the results of a mini-study on moral motivation of behavior of students. They studied the peculiarities of the formation of a moral ideal, provided insight into the dominance of one or another value. These mini-studies allowed us to conclude that the level of development of moral and value orientations of students in experimental groups at the final stage increased significantly compared to the initial one. In the end, the authors conclude that the values and value orientations of modern students can distinguish the following characteristics: the inconsistency of moral orientation; the predominance of instrumental values terminal over; the dominance of pragmatic attitudes; lack of expressed interest in spiritual values and the public interest against the background of inner moral motivation. The prospects of further work with students on the formation of moral motivation of behavior.